Raíces y tubérculos en Ucayali: una mirada desde el método 5 celdas - Bergamini, Nadia; Tristan, Maria Claudia; Sanchez Sanchez, Jose; Rengifo Shuña, Felix Pedro; Grández, Windsor (2025)
This study reports preliminary findings from the Five-Cell Method (M5C), a participatory approach applied in eleven Indigenous and mestizo communities of Ucayali, Peru, to assess the distribution and abundance of underutilized tropical root and tuber crops (NUS). These crops—such as cassava, sachapapa, pituca, huitina, ashipa, dale dale, and aerial yam—hold cultural and nutritional value but are declining due to dietary shifts, commercial crop expansion, and climate pressures. Despite occupying limited farmland, diversity persists through traditional knowledge and in situ practices. Patterns vary by landscape: riverine communities face seed losses and varietal erosion from floods, while highland areas show erosion driven by sociocultural changes. Key vulnerabilities include fragile seed systems, reliance on few households, and loss of traditional knowledge. Strengthening seed networks, revitalizing culinary practices, and promoting community monitoring are essential to sustain agricultural and cultural resilience in Ucayali.